THE REQUALIFICATION OF THE URBAN SPACE OF DELLY IBRAHIM IN ALGIERS BY PERI-URBAN AGRICULTURE - Bacha Nesrine; Hadj Mohamed Naima (International Journal of Innovative Technologies in Social Science, 2024)
Algerian cities are facing uncontrolled urbanization, leading to the loss of vital resources. Algiers, for instance, is rapidly expanding into its outskirts, reducing the agricultural area per inhabitant from 0.82 hectares in 1962 to 0.18 hectares in 2010. This study aims to assess the integration of urban and peri-urban agriculture (UPA) in Delly Ibrahim to restore ecological and economic balance while enhancing local food security.We employ historical analyses, interviews, and field observations to explore the impact of urban sprawl on agricultural practices. Our findings reveal that peri-urban agriculture can play a crucial role in territorial planning, helping to mitigate the negative effects of urbanization. The results indicate that sustainable management of urban resources through UPA can preserve remaining agricultural land, ensure secure local food supplies, and promote environmentally friendly development. Specifically, enhancing green spaces, modernizing traditional agricultural practices, and supporting local food circuits can help balance urban expansion with farmland conservation.In conclusion, integrating UPA in Delly Ibrahim not only addresses the challenges of urban sprawl but also contributes to environmental sustainability and food security. Strengthening these practices is essential for maintaining the region’s agricultural heritage and ecological health.